ANNIHILATION OF GENDER DISCRIMINATION THROUGH INDIAN CONSTITUTION - Krishnajyoti Nath (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The obnoxious discrimination against women and girls has been prevalent all through India for ages. Recognizing this abhorrent practice of gender discrimination, the framers of Indian Constitution enshrined the principle of gender equality in the Constitution. There are many provisions included in this Magna Carta of India with a view to annihilate discriminatory practices based on gender. The Preamble of the Indian Constitution is a brief introductory statement of what the Constitution sets out to achieve. Using the constitutional provisions, we have achieved a certain degree of success in weakening the patriarchal nature of Indian Society, but to achieve gender equality in its truest sense, the society needs to change its mindset on women.